2003
DOI: 10.1200/jco.2003.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lymphatic Mapping on the New Tumor-Node-Metastasis Classification for Colorectal Cancer

Abstract: Conventional examination of lymph nodes for CRC is inadequate for the detection of MM and ITC as described in the new TNM classification. Thus, LM and focused SN analysis should be considered to fully stage CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
12

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 23 publications
1
42
0
12
Order By: Relevance
“…Estes pacientes poderiam se benefi ciar de ressecções cirúrgicas mais amplas (31) . O estudo mostrou que o grupo de LN mais impactante no estádio (pN) é o de LN peritumorais, resultado justifi cado pelo maior número de LN no grupo, pela característica da drenagem linfática (22) (mais próxima do tumor e intensa) e pela provável presença do LN sentinela entre os LN peritumorais (6) , sendo a drenagem linfática aberrante incomum no CCR (4,0%) (10) . Estudos objetivando a otimização do pN mostraram que a análise detalhada do LN sentinela implica em estádio mais acurado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estes pacientes poderiam se benefi ciar de ressecções cirúrgicas mais amplas (31) . O estudo mostrou que o grupo de LN mais impactante no estádio (pN) é o de LN peritumorais, resultado justifi cado pelo maior número de LN no grupo, pela característica da drenagem linfática (22) (mais próxima do tumor e intensa) e pela provável presença do LN sentinela entre os LN peritumorais (6) , sendo a drenagem linfática aberrante incomum no CCR (4,0%) (10) . Estudos objetivando a otimização do pN mostraram que a análise detalhada do LN sentinela implica em estádio mais acurado.…”
Section: Discussionunclassified
“…A avaliação do perfi l qualitativo dos LN tem assumido importância crescente. Nesse contexto, o estudo do LN sentinela (6,10) (LN que recebe drenagem linfática diretamente da lesão primária), do tamanho dos LN (10) e das metástases nos LN (26,32) , da localização dos LN em relação à topografi a da lesão (8) , à proximidade do tumor (11) e de tronco vascular específi co (16) têm sido avaliados em relação ao prognóstico. O uso da imunoistoquímica mostrou-se método efi ciente na detecção de micrometástases (metástases menores que 2 mm) (6) , com impacto no estádio e no prognóstico dos pacientes (6,7,12) .…”
Section: Introductionunclassified
“…Tsioulias et al (34), in their study in which they applied dye injections through colonoscopy to 14 patients who had undergone laparoscopic colectomy, obtained a false-negative result in 1 patient. In the literature, it has been reported that in studies where false-negative rates were relatively high in SLN mapping of colorectal cancers, the reasons were mostly technical errors, lack of experience in SLN mapping, and patients in advanced stages such as stage III-IV (2,9,(13)(14)(15)(16)(17)(18)(19)22,25,(27)(28)(29)(30)(31)(32)(33)(34)(35). While falsenegative rates were reported as 0-75% in the compilation prepared by Cahill et al (26), it is observed that in only 10 of the studies, the false-negative rate is over 30%.…”
Section: Resultsmentioning
confidence: 99%
“…In studies that have used SLN mapping, aberrant lymphatic drainage was reported in 0-10% of the patients (2,9,(13)(14)(15)(16)(17)(18)(19)22,25,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). In our present study, we had no patients with aberrant lymphatic drainage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation